Xuebijing injection mitigates instant blood−mediated inflammatory reaction and enhances intrahepatic islet transplantation via target NF−κB pathway - Zhan, Yixiang; Wang, Yingbo; Zhang, Boya; Zhang, Yijun; Liang, Rui; Yang, Jiuxia; Liu, Tengli; Hu, Xiaoyan; You, Tianyi; Liu, Na; Chen, Yuqi; Liu, Qing; et al. (Frontiers in Immunology, 2025)
IntroductionInstant blood-mediated inflammatory reaction (IBMIR) is a major obstacle in clinical islet transplantation, leading to islet apoptosis and dysfunction due to inflammatory reaction. Xuebijing (XBJ), a traditional Chinese medicine, has been extensively used in the treatment of systemic inflammatory conditions and achieved remarkable effect. Giving these properties, XBJ holds promise in improving the outcomes of intrahepatic islet transplantation through inhibiting IBMIR.MethodsThe xenogeneic islet transplantation model was employed to evaluate the inhibitory effects of XBJ on IBMIR, while the syngeneic transplantation model was used to confirm that XBJ improves the long-term outcomes of intrahepatic islet transplantation through IBMIR suppression. In addition, studies were conducted under inflammatory conditions to demonstrate the protective effects of XBJ on islets in vitro, specifically its ability to preserve islet viability and function in an inflammatory environment.ResultsIn vivo IBMIR model, XBJ significantly inhibited leukocyte infiltration, leading to reduced islet damage. In vitro, XBJ provided direct protection to islets in inflammatory stimulation, preventing apoptosis and preserving islet function. These protective effects were further demonstrated in the syngeneic islet transplantation model, where XBJ markedly improved the outcomes of intrahepatic islet transplantation.DiscussionThis study provides the evidence that XBJ improves islet transplantation outcomes through dual mechanisms targeting the IBMIR. As an already approved drug, XBJ presents a promising and readily translatable adjunctive therapy for clinical intrahepatic islet transplantation.